Metabolomics Profiling and Diagnosis Biomarkers Searching for Drug-Induced Liver Injury Implicated to Polygonum multiflorum: A Cross-Sectional Cohort Study - Huang, Ying; Zhao, Xu; Zhang, Zi-teng; Chen, Shuai-shuai; Li, Shan-shan; Shi, Zhuo; Jing, Jing; Huang, Ang; Guo, Yu-ming; Bai, Zhao-fang; Zou, Zheng-sheng; Xiao, Xiao-he; et al. (Frontiers in Medicine, 2020)
Aim: The diagnosis of drug-induced liver injury (DILI) remains a challenge and the cases of Polygonum multiflorum Thunb.(PM) induced DILI (PM-DILI)have received much attention This study aimed to identify a simple and high-efficiency approach to PM-DILI diagnosis via metabolomics analysis. Methods: Plasma metabolites in 13 PM-DILI patients were profiled by liquid chromatography along with high-resolution mass spectrometry. Meanwhile, the metabolic characteristics of the PM-DILI were compared with that of autoimmune hepatitis (AIH), hepatitis B (HBV), and healthy volunteers. Results: Twenty four metabolites were identified to present significantly different levels in PM-DILI patients compared with HBV and AIH groups. These metabolites were enriched into glucose, amino acids, and sphingolipids metabolisms. Among these essential metabolites, the ratios of P-cresol sulfate vs. phenylalanine and inosine vs. bilirubin were further selected by stepwise decision tree to construct a classification model in order to differentiate PM-DILI from HBV and AIH. The model was highly effective with sensitivity of 92.3% and specificity of 88.9%. Conclusions: This study presents an integrated view of the metabolic features of PM-DILI induced by herbal medicine, and the four-metabolite decision tree technique imparts a potent tool in clinical diagnosis.